Historic evolution of conscientious objection in Italy - Di Pietro, M. L.; Pennacchini, M.; Casini, M. (Medicina e Morale, 2001)
The history of the conscientious objection is an ancient history of which we already have the first testimonies in the Greek civilisation. However, in antiquity the conscientious objection was not a right. It was a testimony of fidelity to absolute values which can arouse admiration too, but that is could not find that hard answers from political part and authority, which was felt defied and threatened. Therefore, the conscientious objection, in the conception in which we mean today, is a conquest of the modern legal civilisation. In Italy the acknowledgement of such institute it has happened to relatively recent times. The aim of this article has been to reconstruct the legal history of the conscientious objection in Italy, both in the context in which it has caught up a regulation or not. The historical reconstruction of the conscientious objection in social and health care field. In medical field [the situation… conscience] have been multiplied the situations that can demand sanitary participations that contract with the own moral and deontological conscience.